PERLINDUNGAN HUKUM ATAS KERUGIAN PASIEN TERHADAP TINDAKAN MEDIS YANG DIDASARKAN PADA PERSETUJUAN - Deni Haryanto (2023)
Agreement for medical action carried out by the patient or the patient's closest family with the Doctor can be held liable in civil or criminal terms. Therefore, it is necessary to study the civil liability of medical personnel for medical actions based on approval of medical actions. Criminal liability of medical personnel for medical actions based on approval of actions medical action and the patient's legal remedies against losses arising from medical action based on the approval of medical action. This research is a normative research, and is descriptive-analytical in nature which describes and analyzes a phenomenon related to patient legal efforts for medical action based on medical consent. The results of the study, civil liability of medical personnel for medical actions based on medical action agreements where medical action agreements have been carried out or agreed between doctors and patients does not rule out being held civilly responsible on condition that there is a loss for violations committed by doctors so that doctors can be held liable Compensation suffered by patients in the form of default related to violation of performance or unlawful acts as stated in Article 1365, Article 1366 and Article 1367 of the Civil Code. The criminal liability of medical personnel for medical actions based on the approval of medical actions is attached to Article 359 of the Criminal Code, namely negligence by causing another person to die, Article 360 paragraph (1) of the Criminal Code, namely negligence which causes a person to become temporarily ill where the elements of criminal responsibility from these articles are fulfilled, namely the ability to be responsible for a doctor, There is negligence on the part of the doctor and the reason for the abolition of the crime in the form of the absence of a forgiving excuse so that the doctor can be punished which must also meet several criteria, namely Duty (obligation), Derelictions of That Duty (Deviation of Obligations), Damage (Losses), Direct Causal Relationship (Related directly). Where the application of Article 359 of the Criminal Code and Article 360 of the Criminal Code is in place of Article 361 of the Criminal Code. The patient's legal efforts against losses arising from medical action are based on the approval of medical action, of course if what happens is an unlawful act or default can be resolved through the non-litigation, while criminal cases must be reported to the police for follow-up in accordance with the applicable criminal procedure law. However, referring to Article 29 of Law No. 36 of 2009 concerning Health, the tendency for legal relations between patients and doctors including medical approval if a criminal or civil event occurs must be resolved first through a mediation process. The Government should revise the Regulation of the Minister of Health No.290/MENKES/PER/III/2008 Concerning Approval of Medical Actions where it must also include issues related to doctors who commit civil violations so that they can provide more legal guarantees to patients or the public. against Regulation of the Minister of Health No.290/MENKES/PER/III/2008 Concerning Approval of Medical Actions where it must also contain issues related to doctors who commit criminal offenses so that they can provide more legal guarantees to patients or the public. Article 29 of Law No.36 of 2009 concerning Health, which tends to provide arrangements regarding the legal relationship between patients and doctors, including medical approval in the event of a criminal or civil incident, must first be resolved through a mediation process, changes must be made by the government or legislative institutions because it does not reflect the principle of justice.